Pengembangan Tambak dengan Sistem Silvofishery di Kawasan Hutan Mangrove Waledan Indah Kecamatan Cantigi Kabupaten Indramayu - A. Pratama Ivo GK; Ivan Chofyan (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Mangrove forests in Indonesia are scattered in several provinces and various islands. The area of mangrove forests in Indonesia is approximately 3.4 million hectares, which is the largest mangrove forest in Asia. Mangrove forest areas can have economic functions, one of which is the development of ponds with a silvofishery system. In Lamarantarung Village, Cantigi District, Indramayu Regency, most of the people who live there make a living as fish farmers. About 70% of the ponds are owned by residents, namely milkfish ponds and 30% of vannamei shrimp ponds. However, pond farmers in Lamarantarung Village have not implemented a silvofishery system pond, which can increase their pond income. As for the background, the writer is interested in making this thesis based on the importance for us to protect mangrove forests because they can preserve ecosystems, apart from that mangrove forests also have economic functions, one of which is the development of ponds with a silvofishery system. The research method used is a descriptive quantitative research method with data collection techniques through literature studies from various journal sources and field surveys which include observation, interviews, and documentation. As for the final results, the authors use the method of farming analysis, anamina models (silvofishery), and community participation analysis. From the results of the analysis that has been carried out, it is found that farming is feasible, because the pond business in the village of Calontarung has advantages and is feasible to cultivate. In addition, from the results of the field survey, it was found that the total area of the pond area was 3,530.8 Ha where the utilization of the mangrove area that could be used as a silvofishery pond was as much as 20%, where if converted the land had an area of 25 Ha. Abstrak. Hutan mangrove di Indonesia tersebar di beberapa provinsi dan berbagai kepulauan. Luasan hutan mangrove di Indonesia kurang lebih 3,4 juta hektar yang merupakan hutan mangrove terluas yang ada di Asia. Kawasan hutan mangrove dapat mempunyai fungsi ekonomi, salah satunya adalah pengembangan tambak dengan system silvofishery. Di Desa Lamarantarung Kecamatan Cantigi Kabupaten Indramayu sebagian besar masyarakat yang tinggal di sana bermata pencaharian sebagai petambak, sekitar 70% tambak milik warga yaitu tambak ikan bandeng dan 30% tambak udang vaname, akan tetapi petani tambak Di Desa Lamarantarung belum menerapkan tambak sistem silvofishery, yang dimana dapat meningkatkan penghasilan tambak mereka. Adapun yang melatar belakangi penulis tertarik untuk membuat skripsi ini didasari karen pentingnya bagi kita untuk menjaga hutan mangrove karena dapat melestarikan ekosistem, selain itu juga hutan mangrove mempunyai fungsi ekonomi, yang salah satunya adalah pengembangan tambak dengan sistem silvofishery. Metode penelitian yang digunakan adalah metode penelitian kuantitatif deskriptip dengan teknik pengumpulan data melalui studi literatur dari berbagai sumber jurnal dan survey kelapangan yang meliputi observasi, wawancara, serta dokumentasi. Adapun untuk hasil akhir penulis menggunakan metode analisis usahatani, model wanamina (silvofishery), dan analisis partisipasi masyarakat. Dari hasil analisis yang telah dilakukan didapatkan bahwa usaha tani layak diusahakan, karena usaha tambak yang ada di desa lamarantarung memiliki keuntungan dan layak diusahakan. Selain itu dari hasil survey ke lapangan di dapatkan jumlah luas lahan tambak seluas 3.530,8 Ha dimana pemanfaatan Kawasan mangrove yang bisa digunakan sebagai tambak silvofishery yaitu sebanyak 20%, dimana jika dikonversikan lahan tersebut memiliki luasan 25 Ha.